Modificação no posicionamento do paciente para o procedimento para prolapso e hemorroidas (PPH): Decúbito ventral com coxim e membros inferiores afastados - Teixeira, Fabio Vieira [UNESP] (2008)
Our aim is to present a modification in patient placement on surgical table for the treatment of prolapsed hemorrhoids by using PPH technique. We propose a modified jackknife position for PPH procedure where the surgeon stays between patient's legs. The modified jackknife position may provide better surgical field with better view of the dentate line which facilitates pursestring confection. In Brazil, the majority of the surgeons prefer lithotomic position for PPH technique based on Longo's first reports. In our opinion, modified jackknife position provides both better surgical field for pursestring placement and better view of the staple line after PPH firing.